The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms23052553
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Theoretical Characterization of a New Small Non-Metal Schiff Base with a Differential Antimicrobial Effect against Gram-Positive Bacteria

Abstract: Searching for adequate and effective compounds displaying antimicrobial activities, especially against Gram-positive bacteria, is an important research area due to the high hospitalization and mortality rates of these bacterial infections in both the human and veterinary fields. In this work, we explored (E)-4-amino-3-((3,5-di-tert-butyl-2-hydroxybenzylidene)amino) benzoic acid (SB-1, harboring an intramolecular hydrogen bond) and (E)-2-((4-nitrobenzilidene)amino)aniline (SB-2), two Schiff bases derivatives. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 58 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…This change of natural variables provides equivalent descriptors to Fukui functions and dual descriptors, namely the local softness [3] and local hypersoftness [13,14,15,16,17,18,19,20,21,22], respectively. They both have demonstrated to be useful for making comparisons of local reactivities among a variety of molecular systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change of natural variables provides equivalent descriptors to Fukui functions and dual descriptors, namely the local softness [3] and local hypersoftness [13,14,15,16,17,18,19,20,21,22], respectively. They both have demonstrated to be useful for making comparisons of local reactivities among a variety of molecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Dual descriptor has the advantage of presenting nucleophilic and electrophilic regions on molecules in just one picture, however it is affected worse than Fukui function as the system's size increases because is an sub-intensive property of degree −2 which means that it is not possible to make comparisons of local reactivities among different molecular systems. To remedy this undesirable behavior it is a common practice to replace Fukui function f (r) with local softness s(r) and dual descriptor f (2) (r) with local hyper-softness s (2) (r) [13,14,15,16,17,18,19,20,21,22] respectively. It will be demonstrated the conceptual support for these replacements.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was reported that, in studies involving only the PSB (i.e., [( E )-2­((3-amino-pyridin-4-ylimino)-methyl)-4,6-diterbutylphenol]), the H-bond stability is independent of the solvent polarity . This same result was also observed with other similar Schiff bases harboring an IHB. ,, Furthermore, confocal microscopy studies performed with these complexes, diluted stock in DMSO, allowed for obtaining successful images in the visible range. , All these results argue for the IHB’s high stability, even in the presence of protic solvents or in cellular environments. Finally, if the IHB was unstable in biological conditions due to protic environments, we would observe that the complexes would exhibit different emissions dependent on the cellular compartment, for example, the cytoplasm (protic medium) or cell membranes (aprotic medium), potentially generating a differential staining.…”
Section: Resultsmentioning
confidence: 61%
“…To study the IHB in more detail, we evaluated the second-order interaction energy through NBO calculations. The interaction energy is related to stabilizing donor–acceptor interactions due to electron delocalization concerning the zeroth-order natural Lewis structure. , In addition, NBO analysis provides an efficient method for studying the participation of the IHB in the stability of N-harboring compounds …”
Section: Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation